Small pieces make the big picture: the etiology of the relationship between executive functions and personality traits - Željka Nikolašević; Snežana Smederevac; Dušanka Mitrović; Petar Čolović; Bojana Dinić; Jasmina Kodžopeljić; Mechthild Prinz; Zoran Budimlija; Vojislava Bugarski Ignjatović (BMC Psychology)
Abstract Background This study primarily aimed to explore the etiology of the phenotypic relationships between personality traits and executive functions. We assessed common genetic and environmental sources of variance in these phenomena by examining different dimensions of the Five Factor Model (FFM) and executive function factors. An additional research question focused on whether specific facets within the FFM share a greater genetic overlap with executive functions compared to broader personality dimensions. Methods The NEO-PI-R, the Wisconsin Card Sorting Test, the Trail Making Test, and verbal fluency tests were applied to a sample of 468 twins from the Serbian Twin Advanced Registry (153 monozygotic twin pairs). Results Several facets from all domains had significant genetic associations with executive functions, with Ideas and Values showing the highest positive correlations, and Order and Vulnerability showing the highest negative genetic correlations. Most phenotypic associations between the two domains of individual differences were almost entirely explained by shared genetic influences. Conclusions These findings underscore the importance of examining personality traits at the facet level, as facet-level analysis provides more detailed insights into the relationship between personality and executive functions than broader personality dimensions. The results emphasize the role of shared genetic influences in shaping both personality and executive abilities, suggesting that future research should investigate the underlying neural mechanisms driving these associations.